Case–Control Study of Breast Cancer in India: Role of PERIOD3 Clock Gene Length Polymorphism and Chronotype. (9th August 2014) - Wirth, Michael D.; Burch, James B.; Hébert, James R.; Kowtal, Pradnya; Mehrotra-Kapoor, Aparna; Steck, Susan E.; Hurley, Thomas G.; Gupta, Prakash C.; Pednekar, Mangesh S.; Youngstedt, Shawn D.; Zhang, Hongmei; Sarin, Rajiv
Abstract : Background : This study examined a PERIOD3 (PER3) gene variable number tandem repeat polymorphism and chronotype as potential BrCA risk factors among Indian women. Methods : This case–control study includeds poradic, histologically confirmed BrCA cases ( n = 255) and controls ( n = 249) from India with data collection from 2010–2012. Results : Women with the 4/5 or 5/5 PER3 genotype had a nonstatistically significant 33% increased odds of BrCA. Cases were more likely to have a morning (OR = 2.43, 95% CI = 1.23–4.81) or evening (OR = 2.55, 95% CI = 1.19–5.47) chronotype. Conclusions : Findings are consistent with the possibility that extremes in chronotype may elicit circadian desynchronization, resulting in increased BrCA susceptibility.